Selling, the new norm : dynamic new methods for a competitive and changing world - Stevens, Drew. (Selling and sales force management collection., 2016)
Why read another book on selling? Simple. Today's client is more informed, more sophisticated, and has more access to information. Selling professionals today need to be keener to fulfill the needs of the client by offering value, and most important trust. In the increasing age and rage of globalization and the Internet, competition rises. Selling professionals today need to determine better ways to reach the economic decision maker and better articulate their value. Selling the New Norm is such a book. This book will provide the tools and templates required to meet today's sales challenges.